Rare Choristoma of the Tarsal Conjunctiva: Critical Inspection Prevents Unnecessary Mutilation - Vetter, Viola Katharina; Correa-Perez, Maria E.; Chaloupka, Karla; Mihic-Probst, Daniela (Case reports in ophthalmology, 2022)
We report a case of a 26-year-old male patient with an incidental finding of a flesh-colored tumor with few vellus hairs on its surface, located on the fornix and the tarsal conjunctiva of the left lower eyelid. Histology of the biopsy showed a choristoma consisting of abundant vellus hairs, sebaceous glands, and sparse lacrimal gland tissue. Recognition of conjunctival vellus hairs is significant and raises the suspected diagnosis of choristoma, which can be confirmed by a small sample biopsy. A complete excision is unnecessary and possible surgical complications can be prevented. Choristomas of the tarsal conjunctiva are very rare and, to our knowledge, this is the first histological documentation of a choristoma containing vellus hair located on the tarsal conjunctiva. In addition, we review the histopathological findings of choristomas and their differential diagnoses.